Approach to the concept of editorial observatory: recommendations for its creation - Colmenares Moreno, Wilson Enrique (Revista General de Información y Documentación, 2021)
The concept ‘observatory’ has been interpreted and used in diverse ways. Its conceptualization is often limited and with no characterization. This affects the perception and credibility that the observatory represents as an instrument. This article presents the results of an approach to the editorial observatory concept that makes it possible to determine some of its main characteristics and, on that basis, to propose recommendations for its creation. An exploratory and descriptive documentary research methodology was designed. 66 bibliographic sources were searched and collected; Of these, 25 were coded using the atlas.ti 8 software. For this, three semantic networks were created grouping 146 codes, in order to answer the questions: What is an observatory? What does it do? and why it does it? Thus, 20 categories were constructed to characterize the websites of three existing editorial observatories. As a result, it was found that an observatory is conceived as a ‘space’ or ‘place; and its main actions are related to 'analyzing' and 'evaluating' 'decision making' and 'monitoring policies'. The characterization carried out through the websites showed the tensions, difficulties and uncertainties that exist between the conceptualization and the implementation of the editorial observatories analyzed. Likewise, this research contributes to knowledge generation so that editorial observatories can be strengthened, designed, or implemented, which should not compete or replicate efforts; its identity is called to supply a higher value to the information to strengthen the production of new knowledge.
Keywords: Bibliographic metadata; Information systems; Information processing; Publishing industry; Text editing